Pre-operative Dynamic Interactive Exploration of Complex Articular Fractures Using a Novel 3D Navigation Tool - Marschollek, M.; Teistler, M.; Bott, O. J.; Stuermer, K. M.; Pretschner, D. P.; Dresing, K. (Methods of Information in Medicine, 2006)
Objectives: Trauma surgeons possess specific anticipative pathoanatomical and procedural domain knowledge that can be used for information extraction from original CT image data. This knowledge so far remains unused in clinical workflow and surgeons do not take an active part in the process of image generation and processing. The objectives of our work are to propose and employ a strategy to directly involve surgeons in a dynamic image exploration process and to exemplarily assess the clinical use of this appoach for pre-operative diagnosis of complex articular fractures.Methods: We used an interactive 3D navigation tool with a novel human-computer interface for the exploration of articular fractures of two selected anatomical structures. The system offers dynamic interaction with a virtual 3D reconstruction model and the possibility to create on-the-fly oblique multiplanar reformations by tracking hand movements. Three expert surgeons performed exemplary explorations and rated the use of the method for preoperative diagnosis in informal interviews.Results: The approach and the system were well received by the three surgeons. The dynamic interaction was rated to be helpful in understanding fracture morphology. Two examples – a radius and a calcaneal fracture – are presented.Conclusions: Surgeons with their specific domain knowledge should be involved in the process of image processing. The benefit of using oblique multiplanar reformations for pre-operative planning in articular fractures appears to be substantial and they should therefore be included in radiological and surgical textbooks. Further evaluation is necessary to assess the use of interactive exploration systems in routine diagnosis.
Keywords: Diagnostic imaging; human-computer interface; articular fractures; visualization; pre-operative planning